2021
DOI: 10.35188/unu-wider/2021/990-7
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric impact of economic policy uncertainty on firm-level investment in South Africa: Firm-level evidence from administrative tax data

Abstract: This paper uses firm-level data and a news-based measure of economic policy uncertainty to provide empirical evidence that economic policy uncertainty has a negative impact on firm-level investment in South Africa. Firms’ investment decisions in response to uncertainty reflect firms’ heterogeneity. Medium-sized firms and, to a different extent, small firms reduce their investment by much more than large firms in response to increased policy uncertainty. The relationship between firms categorized by size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Frieden and Hawkins (2010) presented an expression of the economic concept of asymmetric information with which it is possible to derive the dynamical laws of an economy. Lesame (2021) provided empirical evidence on the asymmetric impact of economic policy uncertainty on firm-level investment in South Africa. He concluded that firms' investment decisions in response to uncertainty reflect firms' heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frieden and Hawkins (2010) presented an expression of the economic concept of asymmetric information with which it is possible to derive the dynamical laws of an economy. Lesame (2021) provided empirical evidence on the asymmetric impact of economic policy uncertainty on firm-level investment in South Africa. He concluded that firms' investment decisions in response to uncertainty reflect firms' heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%